2008
DOI: 10.1021/nn7004365
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Self-Assembly from Building Blocks Synthesized on a Surface in Ultrahigh Vacuum: Kinetic Control and Topo-Chemical Reactions

Abstract: Self-assembly of organic molecules on solid surfaces under ultrahigh vacuum conditions has been the focus of intense study, in particular utilizing the technique of scanning tunneling microscopy. The size and complexity of the organic compounds used in such studies are in general limited by thermal decomposition in the necessary vacuum sublimation step. An interesting alternative approach is to deposit smaller molecular precursors, which react with each other on the surface and form the building blocks for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
79
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(81 citation statements)
references
References 40 publications
0
79
0
2
Order By: Relevance
“…3 Thus, a series of bottom-up fabrication schemes 4 has been developed to realize two-dimensional (2D) layers presenting well-defined open spaces, using hydrogen bonding, [5][6][7][8][9] metal-directed assembly, [10][11][12][13][14] the organization of flexible species, [15][16][17][18] or covalent chemical reactions. 19,20 Nanoporous networks featuring 2D chirality represent a chemically and topologically interesting subclass in this area. [21][22][23][24][25][26] In earlier work, we employed simple ditopic dicarbonitrilepolyphenyl molecular building blocks and studied their selfassembly on the Ag(111) surface.…”
Section: Introductionmentioning
confidence: 99%
“…3 Thus, a series of bottom-up fabrication schemes 4 has been developed to realize two-dimensional (2D) layers presenting well-defined open spaces, using hydrogen bonding, [5][6][7][8][9] metal-directed assembly, [10][11][12][13][14] the organization of flexible species, [15][16][17][18] or covalent chemical reactions. 19,20 Nanoporous networks featuring 2D chirality represent a chemically and topologically interesting subclass in this area. [21][22][23][24][25][26] In earlier work, we employed simple ditopic dicarbonitrilepolyphenyl molecular building blocks and studied their selfassembly on the Ag(111) surface.…”
Section: Introductionmentioning
confidence: 99%
“…Another important investigation demonstrates that the polymerization of Schiff-base reaction can be delicately controlled using the pulse width, avoiding uncontrolled polymerization [33]. Combining with the alkyl group introduced to adjust the lattice constant and size of low dimensional nanostructure (Figure 4(d)) [11,37], Schiff-base coupling reaction occupied a decisive position in the methodology of surface-enhanced polymerization of nanostructures.…”
Section: Schiff-base Reactionmentioning
confidence: 99%
“…[26] Thermally treated metallic substrates were also reported to catalyze the Ullmann coupling reaction and assist organic molecules in forming 1D and 2D polymers. [15,16,[27][28][29] In addition, intermolecular condensation reactions on surfacesfor example, the self-condensation [19] of boronic acids and their co-condensation [20] with polyols, and condensation of carbonyls [21,22] or aldehydes [23,24] with amines-provide alternative options to form covalent linkages. Studies revealed that the number and position of reactive groups, and the symmetry and rigidity of backbones of the precursors play important roles in the resultant structures and morphologies.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, selecting proper reactive components can fabricate 1D or branched polymers, [25,[30][31][32][33][34] 2D chiral architectures, [35] and networks with different periods and pore sizes. [21,24] Highly or-dered large-scale 2D surface covalent organic frameworks (COFs) on highly oriented pyrolytic graphite (HOPG) have also been prepared by means of a self-limiting solid-vapor interface reaction method, mild heating under open or closed environments, [36,37] or even by reaction at the solid-liquid interface at room temperature. [38] In these studies, rigid component molecules were usually employed to build polymers of different dimensions, whereas increasing attention has been given to the adsorption and on-surface synthesis of much larger and more flexible species.…”
Section: Introductionmentioning
confidence: 99%